2010
DOI: 10.1017/s1742170510000025
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse gas emissions from selected Austrian dairy production systems—model calculations considering the effects of land use change

Abstract: The aim of this study was to analyze various Austrian dairy production systems (PS) concerning their greenhouse gas emissions (GHGE) in a life-cycle chain, including effects of land-use change (LUC). Models of eight PS that differ, on the one hand, in their regional location (alpine, uplands and lowlands) and, on the other hand, in their production method (conventional versus organic, including traditional and recently emerging pasture-based dairy farming) were designed.In general, the GHGE-reducing effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 27 publications
1
47
1
6
Order By: Relevance
“…Most studies calculating GHG emissions from dairy farming stop at the dairy farm gate (Lovett et al, 2006;Hö rtenhuber et al, 2010), using different methods for allocating GHG DU 5 dairy cow production unit differing in milk yield per cow per year (6000 kg (DU-6), 8000 kg (DU-8) and 10 000 kg (DU-10)).…”
Section: Allocation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies calculating GHG emissions from dairy farming stop at the dairy farm gate (Lovett et al, 2006;Hö rtenhuber et al, 2010), using different methods for allocating GHG DU 5 dairy cow production unit differing in milk yield per cow per year (6000 kg (DU-6), 8000 kg (DU-8) and 10 000 kg (DU-10)).…”
Section: Allocation Methodsmentioning
confidence: 99%
“…The N 2 O emissions from production of forages and crops (used to feed animals) are an important source of GHG emissions in animal production systems. Lovett et al (2006) and Hö rtenhuber et al (2010) reported that N 2 O emissions from production of forages and crops represent up to 12% of total GHG emissions from Irish and Austrian dairy farms, respectively. The N 2 O emissions in this study were calculated on the basis of N input into the soil in the form of mineral fertilizer, manure and crop residues.…”
Section: Calculation Of Ghg Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent Austrian study, Hörtenhuber et al [63] conducted a ‗life-cycle chain' analyses of eight different dairy production systems representing organic and conventional farms located in alpine, upland and lowland regions. Notably, and rather innovatively, the authors included an estimate for GHG impacts of the estimated land use change (LUC) required to produce concentrates (which ranged from 13% to 24% of total feed intake for various farms), such as soybean production replacing tropical forests.…”
Section: Dairymentioning
confidence: 99%
“…Other considerations are that a longer rearing phase increases the costs (e.g. feed, housing) and the carbon footprint (Hö rtenhuber et al, 2010). In order to optimise dairy farm profitability, it is therefore advisable to aim for early calving (Hultgren et al, 2011) while ensuring that the animals are sufficiently developed.…”
Section: Introductionmentioning
confidence: 99%